PERBEDAAN KEBOCORAN TEPI RESIN KOMPOSIT SILORANE DAN RESIN KOMPOSIT METAKRILAT PADA RESTORASI KAVITAS KELAS I - , AINU ZUHAD SUKATON ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The drawback of methacrylate composite resin is polymerization shrinkage result in a gap development that might cause bacterial or liquid infiltration to dentinal tubules, namely microleakage. Recently, the composite resin development has been focusing on shrink-free composite resin. The latest invention issilorane composite resin that has lower shrinkage and good biocompatibility as well as high strength when compared to that methacrylate composite resin. The purpose of this study was to investigate the microleakage difference between silorane composite resin and methacylate composite resin in class I cavity restoration. Subjects were divided randomly into two groups of 10 each. Class 1 cavity preparation was made in each subject. Group 1, was restored usingsilorane composite resin and group 2, was restored using methacrylate composite resin. Thermocycling using a waterbath with 40C and 600C temperature was carried out on both groups, followed by centrifuging in methylen blue solution with 3000 rpm rotation. Subjects were immersed in artificial saliva for 24 hours, then subjects werecut into two in mesial-distal direction with separating disc and calculated using scoring under stereo microscope with 25 magnification. The results showed that the mean rank in both groups were 6,85 and 14,15 respectively. Analysis using U Mann-Whitney test demonstrated that a significant different in microleakage occurred between group 1 and 2 (p<0,05). It can be concluded that the differences in microleakage occurred between class 1 cavity restoration using silorane and methacrylate composite resins. Silorane composite resin had a lower microleakage than methacrylate composite resin.